Enhancing repo market transparency: The EU Securities Financing Transactions Regulation - Claudio Bassi; Michael Grill; Felix Hermes; Harun Mirza; Charles O'Donnell; Michael Wedow (European Central Bank (ECB), 2024)
The introduction of the Securities Financing Transactions Regulation into EU law provides a unique opportunity to obtain an in-depth understanding of repo markets. Based on the transaction-level data reported under the regulation, this paper presents an overview and key facts about the euro area repo market. We start by providing a description of the dataset, including its regulatory background, as well as highlighting some of its advantages for financial stability analysis. We then go on to present three sets of findings that are highly relevant to financial stability and focus on the dimensions of the different market segments, counterparties, and collateral, including haircut practices. Finally, we outline how the data reported under the regulation can support the policy work of central banks and supervisory authorities. We demonstrate that these data can be used to make several important contributions to enhancing our understanding of the repo market from a financial stability perspective, ultimately assisting international efforts to increase repo market resilience.
Keywords: G10; G18; G23; 330; securities financing transactions; regulation; financial stability